1986
DOI: 10.1083/jcb.103.2.535
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 125I-labeled botulinum neurotoxins with nerve terminals. II. Autoradiographic evidence for its uptake into motor nerves by acceptor-mediated endocytosis.

Abstract: Abstract. Using pharmacological (Simpson, L. L., 1980, J. Pharmacol. Exp. Ther. 212:16-21) and autoradiographic techniques (Black, J. D., and J. O. Dolly, 1986, J. Cell Biol., 103:521-534), it has been shown that botulinum neurotoxin (BoNT) is translocated across the motor nerve terminal membrane to reach a postulated intraterminal target. In the present study, the nature of this uptake process was investigated using electron microscopic autoradiography. It was found that internalization is acceptor-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(93 citation statements)
references
References 48 publications
7
84
1
1
Order By: Relevance
“…In line with previous studies using radioiodinated BoNT/A to label murine motor nerve terminals (27,57,58), gold-tagged BoNT/A-Hc bound predominantly to the membrane of hippocampal neurons at the level of nerve terminals and was internalized in response to stimulation. In the presynaptic nerve terminals, BoNT/A-Hc was detected predominantly in the lumen of synaptic vesicles, with a smaller proportion present in clathrin-coated structures and early endosomes.…”
Section: Discussionsupporting
confidence: 58%
“…In line with previous studies using radioiodinated BoNT/A to label murine motor nerve terminals (27,57,58), gold-tagged BoNT/A-Hc bound predominantly to the membrane of hippocampal neurons at the level of nerve terminals and was internalized in response to stimulation. In the presynaptic nerve terminals, BoNT/A-Hc was detected predominantly in the lumen of synaptic vesicles, with a smaller proportion present in clathrin-coated structures and early endosomes.…”
Section: Discussionsupporting
confidence: 58%
“…[13][14][15][16] Studies on cultured hippocampal neurons from the rat or mouse phrenic nerve of the hemidiaphragm have shown that BTX-A recognizes and enters the ganglioside during neurotransmitter exocytosis when more-active receptors are exposed, exploiting the secretory vesicle recycling pathway. 17,18 Thus, endocytosis of BTX-A is enhanced by synaptic activity.…”
Section: Binding and Internalizationmentioning
confidence: 99%
“…There is evidence suggesting that polysialogangliosides [13] or synaptotagmin [14,15] could act as receptors for the toxins but the data supporting a specific receptor remain equivocal [16]. After binding, the toxin is internalized into an endosome through receptor-mediated endocyctosis [17,18]. The amino-terminal half of the heavy chain (H N ) is believed to participate in the translocation mechanism of the light chain across the endosomal membrane [4,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%